EFEKTIVITAS PROGRAM KELUARGA HARAPAN (PKH) DALAM PENGENTASAN KEMISKINAN DI KELURAHAN SUKAJADI KOTA PRABUMULIH - Dea Vanesa Amelia; Ardi Saputra; Aswasulasikin; Shomedran (STKIP Subang, 2026)
This study aims to determine the effectiveness of the Family Hope Program (PKH) in poverty alleviation in Sukajadi Village, Prabumulih City. The research method used is quantitative with an associative approach. Data were collected through questionnaires distributed to 77 respondents and analyzed using simple linear regression. The results show that the effectiveness of the Family Hope Program has a positive and significant effect on poverty alleviation, with a regression coefficient of 0.501 and a t-value of 6.533 > t-table 1.992 with a significance of 0.001 < 0.05. The coefficient of determination of 36.3% indicates that PKH has a considerable contribution in reducing poverty, particularly in meeting basic needs, improving access to education, and health services. However, there are still challenges such as dependency among some beneficiary families. Therefore, it is recommended that the program implementation focus more on improving economic independence through community empowerment and strengthening assistance quality.